RESPON SIFAT KIMIA TANAH PADA PERLAKUAN KOMPOS KOTORAN TERNAK SAPI DAN TONGKOL JAGUNG - Makapaki, William Oemboe Koedoe; Jawang, Uska Peku (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2025)
This study aims to investigate the impact of a compost fertilizer combination consisting of cow dung and corn cobs on soil chemical properties. This study employed a completely randomized design (CRD) consisting of five treatments: P0 = No Treatment, P1 = 10% / Polybag, P2 = 15% / Polybag, P3 = 20% / Polybag, and P4 = 25% / Polybag. Each treatment was repeated four times. The results showed that the application of compost fertilizer had a significant effect on soil chemical characteristics, specifically organic matter, total N, CEC, P?O?, and K?O. The treatment with the highest increase was in the P4 = 25% / polybag treatment. With every increase in dose, there is an increase in soil chemical characteristics. Compost fertilizer, made from a combination of cow dung and corn cobs, can be used as an organic fertilizer to improve soil quality.